# What is the simplified form of 3/(2x + 5) + 21/(8x^{2} + 26x + 15)

**Solution:**

**Step 1:**

First we need to factorise 8x^{2} + 26x + 15 so that LCM is possible to take for both the terms.

On factorising the term 8x^{2} + 26x + 15 by factorization method

The factors of product 120(8 × 15) are 20 × 6

So that 20 + 6 gives a middle term that is 26 which is the rule of factorization of quadratic equation

8x^{2} + 26x + 15 = 8x^{2} + 20x + 6x +15

= 4x(2x + 5) + 3(2x + 5)

= (2x + 5)(4x + 3)

**Step2:**

⇒3/(2x + 5) + 21/(8x^{2} + 26x + 15) = 3/(2x + 5) + 21/(2x + 5)(4x + 3)

In the first term only 2x + 5 is the term in the denominator which is need to multiplied by (4x + 3) with both numerator and denominator

⇒3/(2x + 5) + 21/(2x + 5)(4x + 3) = [3(4x + 3)/(4x + 3)(2x+5)] + [21/(2x + 5)(4x + 3)]

**Step3:**

After taking LCM for both the terms

⇒ 3/(2x + 5) + 21/(2x + 5)(4x + 3) = [3(4x + 3) + 21 ]/(4x + 3)(2x + 5)

⇒ 3/(2x + 5) + 21/(2x + 5)(4x + 3) =[12x + 9 + 21]/(4x + 3)(2x + 5)

⇒ 3/(2x + 5) + 21/(2x + 5)(4x + 3) =[6x + 30]/(4x + 3)(2x + 5)

⇒ 3/(2x + 5) + 21/(2x + 5)(4x + 3) = 6(x + 5)/(4x + 3)(2x + 5)

## What is the simplified form of 3/(2x + 5) + 21/(8x^{2} + 26x + 15)

**Summary :**

The simplified form of 3/(4x + 3) + 21/(8x^{2} + 26x + 15) is 6(x + 5)/(4x + 3)(2x + 5) .

Since it is not possible to do further simplification 6(x + 5)/(4x + 3)(2x + 5) is the simplified form of the given expression.